PENGEMBANGAN LKPD PEMBELAJARAN IPAS BERBASIS CONTEXTUAL TEACHING LEARNING UNTUK KELAS V MADRASAH IBTIDAIYAH - Nailis Sa’adah; A. Jauhar Fuad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Ngawi, 2025)
ABSTRACT This study aims to develop Contextual Teaching Learning (CTL)-based StudentWorksheets (LKPD) for Science and Social Studies (IPAS) on natural phenomena topics for fifthgrade Islamic Elementary School (MI) students. Using the ADDIE model (Analyze, Design,Development, Implementation, Evaluation) within a Research and Development (R&D) approach,the study involved 11 fifth-grade students at MI Miftahus Sa'adah Ngawi. Data were collectedthrough expert validation (content, design) and practitioner assessments, along with studentresponse questionnaires. The Results of developed LKPD met validity criteria with scores of: (1)86.6% from content experts, (2) 90% from design experts, and (3) 94.2% from practitioners (all